2018
DOI: 10.1038/s41568-018-0001-z
|View full text |Cite|
|
Sign up to set email alerts
|

Structural underpinnings of oestrogen receptor mutations in endocrine therapy resistance

Abstract: Estrogen receptor alpha (ERα), a key driver of breast cancer, normally requires estrogen for activation. Mutations that constitutively activate ERα without the need for hormone are frequently found in endocrine therapy-resistant breast cancer metastases and are associated with poor patient outcomes. The location of these mutations in the ER ligand-binding domain and their impact on receptor conformation suggest that they subvert distinct mechanisms that normally maintain the low basal state of wild-type ERα in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
150
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(155 citation statements)
references
References 142 publications
4
150
0
1
Order By: Relevance
“…Additionally, we see clear allele-specific changes in chromatin accessibility and accompanying transcription factors. Previous studies have also demonstrated allelespecific differences between ER mutations that appear in the structures and molecular effects of mutant ER including differences in their ability to bind cofactors and in their response to hormone therapies (5,6,11,13,17,18,35). These unique differences between ER mutants have significant clinical relevance as ESR1 mutational status could be used to determine treatment strategies that would best serve the patient.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, we see clear allele-specific changes in chromatin accessibility and accompanying transcription factors. Previous studies have also demonstrated allelespecific differences between ER mutations that appear in the structures and molecular effects of mutant ER including differences in their ability to bind cofactors and in their response to hormone therapies (5,6,11,13,17,18,35). These unique differences between ER mutants have significant clinical relevance as ESR1 mutational status could be used to determine treatment strategies that would best serve the patient.…”
Section: Discussionmentioning
confidence: 97%
“…ER mutations occur almost exclusively in the receptor's LBD, which is responsible for binding to estrogens and recruiting cofactors, with the majority of mutations occurring at residues Y537 and D538. Crystal structures of the mutant LBD revealed that mutant ER adopts an active conformation in the absence of estrogen binding and several studies have observed ligandindependent transcriptional regulation, growth, and proliferation of ER mutant breast cancer cells both in vitro and in vivo (4)(5)(6)(10)(11)(12)(13)(14)(15)(16). Large-scale alterations in transcription have also been observed in cells expressing mutant ER (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent examples are ER-based cancer therapies that focus on blocking estrogen action in targeted tissues, with ER α being the main target for treatment of ER-positive breast cancer (Ma et al , 2009). The development of new and improved selective ER modulators is therefore still of high interest for pharmaceutical companies to target tissues selectively and to avoid resistance and adverse effects (Wang et al , 2018; Katzenellenbogen et al , 2018; Baker and Lathe, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies into the molecular and phenotypic consequences of ESR1 LBD mutations have been performed in breast cancer, revealing that the mutations confer estrogen-independent ESR1 activity, which drives gene regulation and cell proliferation in the absence of estrogens (Merenbakh-Lamin et al 2013;Robinson et al 2013;Toy et al 2013;Jeselsohn et al 2014;Bahreini 2017;Toy et al 2017;Zhao 2017;Jeselsohn 2018). Biochemical characterization of the mutations suggests that mutant ESR1 favors the activated conformation of the receptor irrespective of ligand, causing constitutive receptor activity (Merenbakh-Lamin et al 2013;Fanning 2016;Toy et al 2017;Zhao 2017;Katzenellenbogen 2018). Gene expression analyses highlight the ability of mutant ESR1 to regulate canonical ESR1 target genes in the absence of estrogens (Merenbakh-Lamin et al 2013;Robinson et al 2013;Toy et al 2013;Jeselsohn et al 2014;Bahreini 2017;Toy et al 2017;Jeselsohn 2018;Katzenellenbogen 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical characterization of the mutations suggests that mutant ESR1 favors the activated conformation of the receptor irrespective of ligand, causing constitutive receptor activity (Merenbakh-Lamin et al 2013;Fanning 2016;Toy et al 2017;Zhao 2017;Katzenellenbogen 2018). Gene expression analyses highlight the ability of mutant ESR1 to regulate canonical ESR1 target genes in the absence of estrogens (Merenbakh-Lamin et al 2013;Robinson et al 2013;Toy et al 2013;Jeselsohn et al 2014;Bahreini 2017;Toy et al 2017;Jeselsohn 2018;Katzenellenbogen 2018). In addition to ligand-independent regulation of genes that are normally impacted by 17β-estradiol (E2), novel non-E2 regulated genes are also affected by mutant ESR1 (Bahreini 2017;Jeselsohn 2018), suggesting that these mutations may confer additional functionality to ESR1 than just constitutive activity.…”
Section: Introductionmentioning
confidence: 99%